Artesanía en Latinoamérica: Experiencias en el contexto de la Fabricación Digital - Herrera Polo, Pablo C. (2016)
In moments when the artisanship tradition seems to disappear because of industrial production, we analyze cases where digital fabrication and visual programming were used in Latin American craft, encouraged by architects with skills in digital tools. The situations confront artisans with access to digital platforms and internet, use of learned skills, and the need to modify the technological level in their products and processes. Regional initiatives, which could change contemporary design history in the region with the establishing of a trans-disciplinary systematized synergy, show that traditional materials are used and unique components maintain their originality, from a region that attempts to enter into new global markets.